Inappropriate relationships : the unconventional, the disapproved & the forbidden - Goodwin, Robin, 1964-; Cramer, Duncan, 1948- (LEA's series on personal relationships., 2002)
This work explores "inappropriate relationships" across a range of definitions and circumstances. Scholars and researchers in relationship study, interpersonal communication, and sociology should find this work a useful resource for further study and research.